The Simple Math of Writing Well Writing for the 21st Century - Harrop, Jennie A. (Open textbook library., 2018)
Writing guides abound, but The Simple Math of Writing Well is one of a kind. Readers will find its practical approach affirming, encouraging, and informative, and its focus on the basics of linguistic structure releases 21st-century writers to embrace the variety of mediums that define our internet-connected world. As Harrop reminds us in the opening chapters of her book, we write more today than ever before in history: texts, emails, letters, blogs, reports, social media posts, proposals, etc. The Simple Math of Writing Well is the first guide that directly addresses the importance of writing well in the Google age.